The Moderation Role of Work Environment on the Influence of Work Life Balance on Work Stress of GIG Economy Workers in the Online Ojek Driver Group in Jakarta - Susi Adiawaty (Yayasan Sinergi Kawula Muda, 2025)
The purpose of this study was to examine how the work environment affects Life Balance and work-related stress, especially for online motorcycle taxi drivers in Jakarta. The development of the online work economy model provides flexibility, but also brings problems such as income uncertainty and psychological stress, which can increase stress at work. This study used an associative method and involved 150 online motorcycle taxi drivers from five areas of Jakarta. The results showed that work-life balance did not have a significant effect on work stress directly; however, the interaction between work-life balance and work environment showed a moderating effect; a good work environment can improve work-life balance by helping to reduce work stress. This study shows how things like work environment can reduce the stress work experienced by gig economy workers and how important time management is for online motorcycle taxi drivers between their personal life and work.